COVID-19, Pathophysiology and Prospects for Early Detection in Patients with Mild Symptoms of The Controversial Virus in Underdeveloped Countries - Miguel Angel Garcés Villalá; José Andrés Nollen; Sergio David Rico; Gustavo Aníbal Cortez Quiroga; JOSE LUIS CALVO GUIRADO; GABRIEL OSVALDO AUBONE DE LOS RIOS (State Islamic University of Sunan Ampel, 2020)
COVID 19 has spread uniformly across the planet without distinction of hemispheres, borders, or climates. However, underdeveloped countries lack sufficient means to effectively detect and cope with the pandemic. The catastrophic economic situation forces indefinite quarantines to avoid health collapse. The scarcity of massive detection tests has led health personnel, the general population and their rulers to ignorance of the true epidemiological magnitude of SARS-CoV-2. Method: A computerized bibliographic search was performed using the Google search engine of original and review articles indexed by Scopus and WOS, in the PubMed / Medline and Cochrane databases to identify all relevant manuscripts and preprints, notices from professional societies and comments from Experts published from the start of the current epidemic related to mild COVID 19 symptoms. Tools, massive methods for detecting the disease and their low availability in underdeveloped countries were analyzed. Inexpensive and easily accessible methods for testing for the disease were discussed. Result: According to the indexed publications on the incidence of hypoxemia as a symptom and parameter of the evolution of the disease, oxygen saturation of less than 93% was determined as the limit to consider the patient suspected of COVID 19. In addition, it was determined after the analysis of published studies show an average prevalence of anosmia-hyposmia as a mild symptom in 69% of patients infected with COVID 19. Conclusion: Suspected cases of COVID 19 infection could be detected by the presence of its prevalent signs and symptoms. More studies are needed to standardize and validate the postulated screening tests.